ANALISIS KINERJA KEUANGAN PT. TELEKOMUNIKASI INDONESIA TBK TAHUN 2020 - 2024 MENGGUNAKAN RASIO LIKUIDITAS, RASIO PROFITABILITAS, DAN RASIO SOLVABILITAS - Nashia, Keysa Noor Auzora; Pratiwi, Leni Nur (Journal of Fundamental Management (JFM), 2025)
This study aims to analyze the financial performance of PT Telkom Indonesia (Persero) Tbk based on liquidity ratios, profitability ratios, and solvency ratios. The method used is descriptive quantitative analysis, with assessment indicators Current Ratio (CR), Return on Assets (ROA), Return on Equity (ROE), Gross Profit Margin, Debt to Assets Ratio (DAR) and Debt to Equity Ratio (DER). The analysis results show that CR tends to fluctuate and remains below the ideal limit, indicating the need for improvement in current asset management. ROA and ROE also fluctuate downward and have not reached the ideal limit, indicating that the company needs to optimize the use of its assets and equity to generate profit. GPM showed relatively good results as it approached or exceeded the ideal benchmark, suggesting the need for better control over operational expenses. DAR and DER showed fluctuating decreases that reflect the company's efforts to improve the capital structure. Therefore, the company should remain consistent in strengthening its capital structure to reduce its reliance on debt. (Financial Performance, Liquidity Ratio, Profitability Ratio, Solvency Ratio)